PENILAIAN INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA PRA & PASCA PILPRES PADA TANGGAL 09 JULI TAHUN 2014 DENGAN METODE PAIRED SAMPLE TEST - Syahib Natarsyah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This study has the objective to assess the performance of whether there are significant differences Composite Stock Price Index at the Indonesia Stock Exchange before and after the election the President /Vice President of the Republic of Indonesia on July 9, 2014. Model analysis used in this study is Paired Sample Test, the sample used is the daily stock index based on the closing price of each during the 93-day pre-election (transaction on February 19 s / d dated July 8, 2014) and 93 days post-election (transaction from July 10 s/d dated 25 November 2014). The research result showed that (1) the average stock index rose, if before the elections JCI average of 4840.83 with a standard deviation of 129.40, then after the election JCI average rose to 5094.34 with a standard deviation of 80.34 with an increase of 5.25%. (2) the statistical average JCI is there a significant difference with probability p <0.001 where t-count = - 14.438 with testing significant 2 tail.